Prevalensi dan Distribusi Penderita Stomatitis Aftosa Rekuren (SAR) di Klinik Penyakit Mulut RSGM FKG Universitas Jember pada Tahun 2014 (Prevalence and Distribution of Patients Recurrent Aphthous Stomatitis ( RAS ) in Oral Medicine Departement of Dental - Annisa Sulistiani; Sri Hernawati; Ayu Mashartini P (Pustaka Kesehatan, 2017)
Background: Recurrent Aphthous Stomatitis (RAS) is a disorder characterized byrecurring ulcers confined to the oral mucosa with no other signs of disease. RAS isclassified according to three classification, there are RAS minor, RAS mayor, and RASherpetisformis. RAS prevalence of general population ranges from 5%-66%. Purpose:This study aimed to obtain the prevalence and distribution of patients suffering from RASin Oral Medicine Departement of Dental Hospital, Dentistry Faculty, University of Jemberin 2014. Method: This study used descriptive study with retrospective approach andpurposive sampling. The population of this study is all patients of Oral MedicineDepartement of Dental Hospital, Dentistry Faculty, University of Jember in 2014 as manyas 1073 peoples. Result and Conclution: The result showed that 146 patients sufferSAR (14%) from 1037 patients in Oral Medicine Departement of Dental Hospital,Dentistry Faculty, University of Jember on January until December 2014. There were97% of patients had RAS minor, 3% of patients had RAS mayor, and 0% of patients hadRAS herpetisformis from 146 patients with RAS. RAS can occur in women or men andchildren or adults, the result of this research showed that RAS was most common inwomen, that was 70% and the age groups of 12-24 years was 54%.Keywords: Distribution, Prevalence, Recurrent Aphthous Stomatitis (RAS)